2011
DOI: 10.1021/np100826q
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Triterpenoids: Potent Agents for Prevention and Treatment of Tissue Injury Caused by Inflammatory and Oxidative Stress

Abstract: We review the original rationale for the development and the chemistry of a series of new synthetic oleanane triterpenoids (SO), based on oleanolic acid (1) as a starting material. Many of the new compounds that have been made, such as 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (“CDDO”, 8), are highly potent (activities found at levels below 1 nM) anti-inflammatory agents, as measured by their ability to block the cellular synthesis of the enzyme inducible nitric oxide synthase (iNOS) in activated macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
270
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(278 citation statements)
references
References 71 publications
5
270
1
2
Order By: Relevance
“…The synthetic triterpenoid compounds belonging to the bardoxolone methyl (CDDO-Methyl ester) family are potent Nrf2 activators [24,25]. By interacting with the keap1 molecule these compounds facilitate nuclear translocation of Nrf2 and expression of its target genes [26].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic triterpenoid compounds belonging to the bardoxolone methyl (CDDO-Methyl ester) family are potent Nrf2 activators [24,25]. By interacting with the keap1 molecule these compounds facilitate nuclear translocation of Nrf2 and expression of its target genes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they show remarkable protective efficacy in a number of preclinical animal models of chronic disease, including carcinogenesis, cardiovascular disease, and neurodegeneration, and in early clinical trials (reviewed in refs. 15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Novel synthetic triterpenoids which mimic natural triterpenoids in physical and chemical properties have been found to be effective in suppressing inflammation and inducing apoptosis in a wide variety of tumor cells via diverse mechanisms [16,164]. This was first established by the exceptional ability of synthetic oleanane triterpenoids to inhibit inducible NOS induced by TNF-a, IL-1 and IFN-c [191].…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%
“…Proteomic analysis has led to the identification of important protein targets of synthetic triterpenoids. In many instances, it has been observed that these compounds bind to the active cysteine residue in the proteins [16]. The key proteins that have been reported to be modulated by oleanane triterpenoids are Keap 1 [193,194], IKK, IkBa and NF-jB [164,166], JAK1 and STAT3 [165,195,196], PTEN [197], AKT [14,198,199], mTOR [200], ROS [201], DR5 and CHOP [202], GSK3b [203], cFLIP and VEGF [204,205], mitochondrial membrane potential [206], and cell cycle arrest [198,207,208].…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation